مدينة وهران النشأة و التطور و الدور في العصر الوسيط - غانية, البشير (جامعة الوادي - University of Eloued, 2021)
مدينة وهران حاضرة من حواضر المغرب الاوسط الجزائر الحالية ،اكتست اهميتها الحضارية مند فجر التاريخ من خلال موقعها الساحلي المطل على الحوض الغربي للبحر الابيض المتوسط ، اذ ساهم ذلك الموقع الجيوسترتيجي في ان تكون حلقة اتصال جغرافي افقية بين المغربين الأدنى و الأقصى وعمودية بين عالم البحر الابيض المتوسط الشمالي وبلاد السودان الغربي ، وقد مكنها كذلك هذا الموقع بأن تكون مصدر تواصل بين المغرب الأـوسط و الأندلس الذي تجلى في عدة أشكال مفرزا مدينة فاخرة من مدن المغرب الأوسط عامرة ذات روح أندلسية مغربية ،وما فتئت كذلك أن باتت اليوم عروس البحر الأبيض المتوسط. The city of Oran is present from the present Maghreb metropolises of Algeria. It gained its cultural significance from the dawn of history through its coastal location overlooking the western basin of the Mediterranean. The northern Mediterranean and western Sudan, and this site has also enabled it to be a source of communication between the Central Morocco and Andalusia, which was manifested in several forms as a luxury city from the cities of the Central Maghreb, full of Andalusian Moroccan spirit, and it has been so well that today it is the bride of the White Sea The average.
مقال
Keywords: وهران ، المغرب الأوسط، الأندلس، البربر ،بنو مسكين; Oran; central maghrib; Andalusia;Berbers; Banu Miskin